METHODOLOGY FOR TEACHING WRESTLING TECHNIQUES AND TACTICS - Xursanali Kurbonalievich Umarov (Bright Mind Publishing, 2025)
The article describes a summary of the training of wrestlers in technique and tactical movements
Keywords: Wrestling, mat, movement, method, tactics, technique, competition, single, distance.